To multiply the polynomial expression \((\frac{1}{2^2} - 3)(4y^3 + 5x^2)\), we first simplify the constant coefficient.
-
Calculate \(\frac{1}{2^2}\): \[ \frac{1}{2^2} = \frac{1}{4} \] So, \(\frac{1}{2^2} - 3\) becomes: \[ \frac{1}{4} - 3 = \frac{1}{4} - \frac{12}{4} = -\frac{11}{4} \]
-
Now we have: \[ -\frac{11}{4}(4y^3 + 5x^2) \]
-
We distribute \(-\frac{11}{4}\):
- Multiply \(-\frac{11}{4}\) by \(4y^3\): \[ -\frac{11}{4} \cdot 4y^3 = -11y^3 \]
- Multiply \(-\frac{11}{4}\) by \(5x^2\): \[ -\frac{11}{4} \cdot 5x^2 = -\frac{55}{4}x^2 \]
-
Combine the results: \[ -11y^3 - \frac{55}{4}x^2 \]
Thus, the final result is: \[ -11y^3 - \frac{55}{4}x^2 \]